NON-COMPLIANCE WITH STANDARD ACCOUNTING PRACTICES BY SMALL AND MEDIUM SCALE ENTERPRISES IN SRI LANKA - Abeygunasekera, A.W.J.C.; Fonseka, A.T. (My University, 2012)
This study is done in relation to the factors leading to non-compliance with Standard accounting practices by the small and medium scale enterprises (SMEs), specifically in relation to a developing country like Sri Lanka. The main objectives of the study focused on identifying the nature of the accounting practices and the factors leading to non-compliance with standard accounting practices by the SMEs. Efforts are made to examine the possible causes for noncompliance with the Standard accounting practices by the SMEs in Sri Lanka and the researcher expects that this study would fill the knowledge gap. The researcher used structured interviews to collect data and has selected 30 SMEs in the manufacturing sector and 10 auditors for the study. Two interview guides are prepared by the researcher for the SME owners, and for the Auditors. In the conceptual model the non-compliance is considered as the dependent variable and the independent variables are the cost of adherence to accounting standards, knowledge and competence of the owners, lack of qualified employees, relevance of standard guidelines and parties interested in the financial reports. The key finding is that, higher cost of adherence to accounting standards, lack of knowledge and competence of the owners, lack of qualified employees, and unavailability of parties interested in the financial reports other than owner is leading to non-compliance and the relevance of standard guidelines does not have a relationship with non-compliance. The non-compliance with Standard accounting practices is not only due to SMEs ‘can’t comply’ with them, but also due to they ‘won’t comply’ with them even when the are able to comply. The researcher finally makes recommendations to the policy makers, government and professional accounting bodies to design the policies and frameworks to ensure SMEs’ compliance with standard accounting practices.